EU transfers and euroscepticism: can’t buy me love? - Borin, Alessandro; Macchi, Elisa; Mancini, Michele (Economic policy, 2021)
SUMMARY The future of an institution, such as the European Union, ultimately depends on people’s support. This paper investigates whether EU redistributive policies have improved public attitudes towards European integration, both in terms of public opinion and political preferences. We focus on Cohesion Policy funds, whose allocation allows us to single out these effects by means of a regression discontinuity approach. The results show that EU transfers have mitigated the rise of Eurosceptical attitudes and reduced political consensus for anti-EU parties. The effects are homogeneous across different socio-economic groups, including the most disadvantaged ones. The improvement in public support for the EU does not appear to be exclusively a spillover of the positive economic effect of funding; we show evidence suggesting the existence of a ‘reciprocity-effect’ channel, that is, citizens in recipient regions recognize the beneficial role of the EU as the source of funding.